A aprendizagem cooperativa nas aulas de matemática : uma experiência nas turmas de 8º e 9º anos - Gouvêa, Mariangela Salviato Balbão (Universidade Federal de São Carlos, 2012)
The objective of this study is to establish whether mathematical activities, prepared based on cooperative learning, produce changes in how students learn and confront with mathematics. Thus, were designed, developed and analyzed six math classes cooperatives, which occurred in an 8 and a 9 th grade of elementary education at a private school. The proposed group of activities consists of mathematical problems written in the form of clue cards. Each group receives an envelope containing six cards, which must be distributed among team members. To solve the problem all students must contribute explaining their clues and sharing ideas. The teacher provides various materials to support the activities such as ruler, squares, compasses, paper, scissors, calculators, colored cubes, dice, straws, beans, charts etc. The results obtained by each group are described in the answer sheets, previously prepared by the teacher. Before and after cooperative classes, a questionnaire was applied in order to know the opinion of students about group work and their skills in mathematics. The results achieved with the cooperative activities were fruitful discussions on mathematical concepts and their properties, greater clarity from teachers regarding students' mathematical difficulties, greater social involvement, respect for ideas and opinions of group members, ability to represent mathematical situations by using concrete materials, drawings, graphics and text.
Keywords: Matemática - estudo e ensino; Aprendizagem cooperativa; Jogos em educação matemática; Mathematics Teaching; Cooperative learning; Mathematical games; CIENCIAS EXATAS E DA TERRA::MATEMATICA